PENGALAMAN PERAWAT DALAM MELAKSANAKAN TRIASE PADA KUNJUNGAN MASSAL DI RUANG IGD RUMAH SAKIT KEBONJATI BANDUNG - Yunita Sarah Nadeak; Tiarmaida Sitio; Andi sukandi (Jurnal Kesehatan, 2023)
Triage is a dynamic process of decision making to prioritize patients according to their medical condition and life expectancy when they arrive at the emergency room (Gerdtz and Bucknall 2001, Cooper, et al, 2020). Patients who come at the same time will exceed the capacity of available personnel. As a result, there is an imbalance in the capacity of the ER team and the number of patients. Facts show that the number of nurses in the emergency room triage room at Kebonjati Hospital is only 3 people in each shift. It is clear that this number is not ideal, especially when mass visits occur, because there will be an imbalance in the number of nurses and patients who come. To find out the experience of nurses in carrying out triage during mass visits in the emergency room at Kebonjati Hospital, Bandung. This research was conducted using an interpretive phenomenological qualitative design approach. The sample in this study was 12 nurses who were collected using tital sampling. In accordance with the research results obtained, there are 4 themes. The themes obtained from data analysis of nurses' experiences in carrying out triage during mass visits in the emergency room of the first type C referral hospital, Kebonjati Hospital, Bandung, are: 1. The triage mechanism has changed 2. The triage system is not yet adequate. 3. Expect changes to the IGD4 policy. Prioritizing the IEC Strategy, where these themes ultimately converge to a theme, namely "the spirit of change amidst an inadequate triage system for mass visits.